Kualitas Hidup Pada Pasien Gagal Ginjal Kronik (GGK) - Titin Supriatin; Angella Nur Mustika; Intan Ayu Maharani Putri; Nurkhalifah Khumaeroh; Rizky Adhitya Setiawan; Ridho Fabhio Ramadhan (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Chronic kidney disease, commonly abbreviated as CKD, is a condition characterized by a gradual decline in kidney function over a period of three months or more. Between 2018 and 2021, there was a specific increase in cases of kidney failure. According to statistics, 1,602,059 Indonesian residents, including 33,828 in West Java, were affected by kidney failure in 2018. This number is projected to continue rising (Riskesdas, 2020). Globally, the number of End-Stage Renal Disease (ESRD) patients reached 3,200,000 in 2020. Kidney disease typically affects individuals between the ages of 46 and 50. The objective of this literature review is to determine the quality of life of patients with chronic kidney disease (CKD). This review utilized Google Scholar and EBSCO databases, employing keywords such as "Chronic Kidney Disease" AND "Management of patients with kidney failure". Fifteen journals meeting the inclusion criteria were selected, published between 2020 and 2024. The predominant study design was cross-sectional, with stratified and purposive sampling methods commonly used. This review employed descriptive and analytical observational methods, utilizing the chi-square test. This literature review demonstrates that sociodemographic factors, including age, education, occupation, and ethnicity, significantly impact the quality of life of end-stage renal disease patients undergoing dialysis. Furthermore, the study highlights a strong association between clinical status and psychological distress among these patients. To enhance the quality of life of these individuals, comprehensive healthcare interventions, particularly psychological support and education, are essential.